Exploring Indonesian Millennials Muzakkis’ insight of Paying Zakat in Digital Era - Bella Jastacia; Dinda Ismu Asyifa (ITB AAS INDONESIA Surakarta, 2021)
Indonesia has 25.8% millennials, which this number counted as huge enough. It means that Indonesia has many youth generations. Millennials is a generation that like new things, especially technology. So, they understand technology and they can operate technology devices such as laptop or mobile phones. In this globalization era, everything is digital, especially in paying zakat. For millennials, it is easy to pay zakat by using their device through financial technology that has features to pay zakat. Thus, even though they understand the technology and they have ability to pay zakat digitally, it is essential to explore their insight of paying zakat in digital ways. This research explored Indonesia millennials Muzakki’s insight of Paying zakat in digital era from millennials with economic backgrounds and millennials without economic background. There were 135 participants from this research. This research used a quantitative method by applying survey approach. However, there was a significant difference of millennials Muzakki with economic background and millennials Muzaki without economic background.